2011
DOI: 10.1007/s00464-011-1909-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy after a quarter century: why do we still convert?

Abstract: Background Laparoscopic cholecystectomy (LC) is the gold standard procedure for gallbladder removal. However, conversion to open surgery is sometimes needed. The factors underlying a surgeon's decision to convert a laparoscopic case to an open case are complex and poorly understood. With decreasing experience in open cholecystectomy, this procedure is however no longer the “safe” alternative it once was. With such an impending paradigm shift, this study aimed to identify the main reasons for conversion and ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 22 publications
(21 reference statements)
0
22
0
3
Order By: Relevance
“…In converted cases, the extent of dissection before conversion was classified as minimal, some, and extensive dissection, according to a previous report. 14 …”
Section: Methodsmentioning
confidence: 99%
“…In converted cases, the extent of dissection before conversion was classified as minimal, some, and extensive dissection, according to a previous report. 14 …”
Section: Methodsmentioning
confidence: 99%
“…Conversion to OC may be required in about 5-10% [5,6,7,8,9,10,11]. Many causes for conversion have been reported in the literature, including patient-related and disease-related factors, and some reports outlined different risk factors for conversion to OC [4,9,12].…”
Section: Introductionmentioning
confidence: 99%
“…Both open conversion and fundus-first technique are controversial as to whether they are useful in avoiding or reducing the risk of BDI. Lengyel et al [46] did not find a significant difference in the complication rate between laparoscopic and open conversion groups and concluded that open conversion should be determined only after surgeons make a genuine effort at a laparoscopic approach. All extreme vasculobiliary injuries reported by Strasberg and Gouma [47] occurred during conversion to an open cholecystectomy and fundus-first technique, raising a red flag to rely on these procedures without knowing their disadvantages.…”
Section: Discussionmentioning
confidence: 98%